Trastuzumab Deruxtecan plus Pertuzumab for HER2-positive metastatic breast cancer - Tolaney, Sara; Jiang, Zefei; Zhang, Qingyuan; Barroso-Sousa, Romualdo; Park, Yeon Hee; Rimawi, Mothaffar F.; Saura, Cristina; Schneeweiss, Andreas; Toi, Masakazu; Chae, Yee Soo; Kemal, Yasemin; Chaudhari, Mukesh; et al. (The New England journal of medicine, 2025)
Background: Trastuzumab deruxtecan has shown efficacy in patients with previously treated human epidermal growth factor receptor 2 (HER2)–positive advanced or metastatic breast cancer. The efficacy and safety of trastuzumab deruxtecan in patients with no previous therapy for HER2-positive advanced or metastatic breast cancer are unclear. Methods: We conducted a phase 3 trial involving patients with HER2-positive advanced or metastatic breast cancer and no previous chemotherapy or HER2-directed therapy for metastatic disease. Patients were randomly assigned in a 1:1:1 ratio to receive trastuzumab deruxtecan plus pertuzumab; trastuzumab deruxtecan plus placebo; or a taxane, trastuzumab, and pertuzumab (THP). The primary end point was progression-free survival as assessed by blinded independent central review. Secondary end points included objective response, duration of response, and safety. Results: For this prespecified interim analysis, data for trastuzumab deruxtecan plus pertuzumab and for THP are reported; data for trastuzumab deruxtecan plus placebo remain blinded until the final analysis of progression-free survival. At the data-cutoff date (February 26, 2025), the median progression-free survival was 40.7 months with trastuzumab deruxtecan plus pertuzumab (383 patients) and 26.9 months with THP (387 patients) (hazard ratio for progression or death, 0.56; 95% confidence interval [CI], 0.44 to 0.71; P<0.00001 [P-value boundary for superiority, 0.00043]). The incidence of a confirmed response was 85.1% with trastuzumab deruxtecan plus pertuzumab and 78.6% with THP (complete responses in 15.1% and 8.5%, respectively), with a median duration of response of 39.2 months and 26.4 months. Safety was consistent with the known profiles of the individual treatments. The incidence of grade 3 or higher adverse events was 63.5% with trastuzumab deruxtecan plus pertuzumab and 62.3% with THP; the most common were neutropenia, hypokalemia, and anemia with trastuzumab deruxtecan plus pertuzumab and neutropenia, leukopenia, and diarrhea with THP. Adjudicated drug-related interstitial lung disease or pneumonitis occurred in 12.1% of patients receiving trastuzumab deruxtecan plus pertuzumab (grade 1 or 2 in 44 patients and grade 5 [death] in 2 patients) and in 1.0% of those receiving THP (all grade 1 or 2). Conclusions: Trastuzumab deruxtecan plus pertuzumab led to a significantly lower risk of progression or death than THP when used as first-line treatment for HER2-positive advanced or metastatic breast cancer, with no new safety signals. (Funded by AstraZeneca and Daiichi Sankyo; DESTINY-Breast09 ClinicalTrials.gov number, NCT04784715.)
Veröffentlicht: 29. Oktober 2025
Gesehen am 19.12.2025